New species of Paktongius and convergent evolution of the gonyleptoid-like habitus in Southeast Asian Assamiidae (Opiliones: Laniatores) - Klementz, Benjamin C.; Sharma, Prashant P. (Zootaxa, 2023)
The armored harvestman family Assamiidae (Arachnida: Opiliones: Laniatores) is widely distributed throughout the Old World tropics, specifically throughout tropical Asia and Central Africa. However, the systematics and intrafamilial relationships of the group remain poorly understood. This can be largely attributed to the complicated taxonomic history of the group, which is exemplified by poorly supported subfamily classifications and the prevalence of monotypic genera. Here, we describe four new species of the formerly monotypic genus Paktongius Suzuki, 1969, using specimens collected from Laos, Thailand, and West Malaysia, suggesting a degree of microendemism within the group, which underscores the need for greater sampling of the southeast Asian arachnofauna. Recent phylogenetic analysis has also suggested that Mysorea thaiensis Suzuki, 1985 nests within a clade composed of Paktongius distinctus Suzuki, 1969 and the species described herein (P. suzukii sp. nov., P. spiculosus sp. nov., P. paritensis sp. nov., P. furculus sp. nov.). We therefore transfer Mysorea thaiensis to Paktongius (P. thaiensis comb. nov.). We also comment on the unique morphology of this highly derived group of harvestmen, which appears to suggest convergent evolution of the gonyleptoid-like morphology, complete with the characteristic exaggerated leg four coxae and laterally expanded scutum.